Contextualising men's role and participation in PMTCT programmes in Malawi and Zambia: A hegemonic masculinity perspective. Issue 9 (2nd September 2022) - Mweemba, Oliver; Zimba, Chifundo; Chi, Benjamin H.; Chibwe, Kasapo F.; Dunda, Wezi; Freeborn, Kellie; Maman, Suzanne; Matenga, Tulani Francis L.; Phanga, Twambilile; Rosenberg, Nora; Mutale, Wilbroad
ABSTRACT: This study sought to explore and contextualise the man's role in antenatal services, and the barriers and strategies for engaging men in prevention of mother-to-child HIV transmission (PMTCT). We conducted 143 interviews with pregnant and breastfeeding women, male partners, health workers and policy makers in Malawi and Zambia. We employed thematic and critical discourse analysis using the hegemonic masculinity perspective. We found that men's roles in PMTCT reflected hegemonic masculinities. As breadwinners, men supported their partners with material and financial resources. As decision makers, men were involved in decision making on the health of their partners. As social protectors, men supported their partners in accessing and adhering to antenatal care, HIV treatment and care. Barriers and challenges to male involvement in antenatal care were often the result of conflict between the clinic operating hours and men's working hours, the perception of antenatal care services as female spaces, and men's fear of HIV testing. Proposed strategies to increase male engagement in PMTCT included sensitising men about HIV and pregnancy; engaging leaders and employers, providing services outside working hours, and providing incentives. We conclude that men's role and participation in PMTCT services are an extension and adaptation of hegemonic masculinities.